OʻZBEK XALQ OʻLANLARIDA QOʻLLANILGAN TROPLAR TABIATI - Turgʻunov, Sh.D. (SCIENCE and SOCIETY, 2024)
The text of Uzbek folk songs (ulan) widely uses as means of artistic depiction, in particular tropes. Clarification of the poetic role of metaphors, metonymy, synecdoche and tropes in the composition of folk lancers is one of the pressing problems facing our folklore research. This article discusses the same issues.